DEVELOPMENT OF DIGITAL FLUOROSCOPIC PROTOTYPE FOR MANUFACTURING INDUSTRIES - Demon Handoyo; Agus Cahyono; Kristedjo Kurnianto; Andeka TS (Instrumentasi, 2017)
Many X-ray applications in non-destructive testing have provided lots of benefits for manufacturing industries. A number of shortcomings of the use of film to capture images and the high-cost of digital radiography equipments make a low-cost equipment that can generate clean and clear images really expected. This paper describes the construction of such equipment. Based on the engineering principles, a prototype of digital fluoroscopy consisting of radioscopy box, belt conveyor, and controlling instrument, has been completed. The design employs fluorescent screen, mirror, and digital camera to record and transmit the images of test specimen to a computer for image processing. A LabView-based program has been built for conveyor control, camera control, and image recording, storing, and processing. Calibration and image enhancement processes have been applied to the images obtained. The success of the development of this equipment is represented by the highly clean and clear quality of the generated images.